First Episode Psychosis in Patients Aged 18 to 30 Admitted Involuntarily: Characteristics and Risk Factors for Functional Non-Remission - Maria El Helou; Matthieu Hein; Beni-Champion Cimpaye; Benjamin Wacquier; Anaïs Mungo (Brain Sciences, 2025)
Introduction: This study aimed to explore the clinical and psychosocial characteristics associated with functional non-remission in young adults involuntarily hospitalized for a first episode of psychosis (FEP), focusing on the role of duration of untreated psychosis (DUP) and contextual vulnerabilities. Material and method: We conducted a retrospective monocentric study including 123 patients aged 18–30 who were involuntarily admitted between 2013 and 2023 for a first psychotic episode. Sociodemographic, clinical, and care-related data were extracted from medical records. Functional remission was defined as a Global Assessment of Functioning (GAF) score ≥70 at discharge. Univariate and multivariate logistic regressions were used to identify predictors of functional non-remission. Results: Only 48.8% of patients achieved functional remission at discharge. Social isolation, low socioeconomic status, unemployment, lack of structured activities, and a DUP ≥ 4 weeks were significantly associated with functional non-remission. After multivariate logistic regressions, DUP ≥ 4 weeks remained an independent predictor of functional non-remission. Conclusions: Involuntary admission per se was not a direct predictor of poor outcome. Our findings highlight the critical role of prolonged DUP and psychosocial vulnerability in the trajectory of early psychosis. Early detection strategies, psychosocial support integration, and individualized care planning are essential to improve outcomes among young people experiencing FEP under compulsory admission.